Innovative spectrofluorometric method for determination of harmaline and harmine in different matrices - Ahmed H. Abdelazim; Majed A. Algarni; Atiah H. Almalki (Scientific Reports, 2023)
Abstract Harmaline and harmine are naturally occurring closely related β-carboline alkaloids found in Peganum and Banisteriopsis plants. They have historical significance in traditional practices due to their potential psychoactive and therapeutic properties. Herein, a highly sensitive spectrofluorometric method was developed for the quantifying of harmaline and harmine in diverse matrices, including pure forms, seed samples, and spiked plasma. The procedures lie in addressing the challenge of overlapping fluorescence spectra exhibited by harmaline and harmine through the incorporation of hydroxypropyl-β-cyclodextrin, altering their chemical properties and fluorescence characteristics. Synchronous fluorescence measurements coupled with first derivative mathematical technique make it possible to distinguish between the harmaline and harmine at 419 and 456 nm, respectively. The method effectiveness is demonstrated through spectral analysis, optimization of the measurement conditions, adopting validation parameters and application to the pure form, seed samples and spiked human plasma. This methodology facilitates accurate determination of these alkaloids over the concentration range of 10─200 ng/mL. Thus, the developed approach provides a robust mean for the precise determination of harmaline and harmine, contributing to analytical chemistry's ongoing efforts to address complex challenges in quantification across diverse matrices.